Populist Strategies in the Political Advertising Discourse of the French National Front - Khoudary, Rana N. (REiLA : Journal of Research and Innovation in Language, 2021)
This study investigates the discourse of the French right-wing political party National Front (FN) through a qualitative Critical Discourse Analysis approach examining their electoral campaign material from 2011 until 2017. The findings reveal that the FN adopts typical populist tropes and strategies to broaden its electoral base and win popular support. At the core of their discourse lie binary conceptualisations constructing an in-group (the FN, the people) and an out-group (political individuals and entities, immigrants) in a scheme of opposition, typically attributing positive qualities to the former and negative values to the latter. The linguistic construction of the Self and the Other was achieved through the use of metaphor and speech acts, in addition to other discursive strategies involving the appeal to negative emotions. In accordance with van Dijk’s ideological square, metaphors reveal a sharp polarisation in the depiction of the Self and the Other, mainly through the FN's positive self-presentation in terms of benevolent and optimistic metaphors. In contrast, the Other is mainly portrayed through war metaphors. Similarly, through the use of speech acts, the FN blames, accuses and criticises the Other, holding it accountable for the French people’s grievances, while the Self (in the person of the FN’s leader Marine Le Pen) is assertive, firm and determined in its defence of the nation and the people. Linguistic strategies are ultimately reinforced through semiotic representations, enhancing the us/them dichotomy.